2012
DOI: 10.1128/aem.01558-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Mating Type Distribution of Tuber melanosporum and Their Significance to Truffle Cultivation in Artificially Planted Truffiéres in Australia

Abstract: Tuber melanosporum is a truffle native to Europe and is cultivated in countries such as Australia for the gastronomic market, where production yields are often lower than expected. We assessed the genetic diversity of T. melanosporum with six microsatellite loci to assess the effect of genetic drift on truffle yield in Australia. Genetic diversity as assessed on 210 ascocarps revealed a higher allelic diversity compared to previous studies from Europe, suggesting a possible genetic expansion and/or multiple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Would this be the case for artificially inoculated seedlings transplanted to field conditions? Observations made in Australia by Linde and Selmes (2012) on T. melanosporum plantations set up between 2003 and 2007 showed that out of 16 productive trees, 8 displayed only one mating type while on the remaining 8 plants, ectomycorrhizas of both mating types were present, with slightly irregular distribution. Murat et al (2013) compared two older plantations: one in Italy (Montemartano, Q. pubescens and Quercus ilex planted in 1995) and one in France (Rollainville, C. avellana, planted in 1991).…”
Section: T Melanosporum Is a Heterothallic Fungusmentioning
confidence: 99%
See 2 more Smart Citations
“…Would this be the case for artificially inoculated seedlings transplanted to field conditions? Observations made in Australia by Linde and Selmes (2012) on T. melanosporum plantations set up between 2003 and 2007 showed that out of 16 productive trees, 8 displayed only one mating type while on the remaining 8 plants, ectomycorrhizas of both mating types were present, with slightly irregular distribution. Murat et al (2013) compared two older plantations: one in Italy (Montemartano, Q. pubescens and Quercus ilex planted in 1995) and one in France (Rollainville, C. avellana, planted in 1991).…”
Section: T Melanosporum Is a Heterothallic Fungusmentioning
confidence: 99%
“…However, the close proximity of two potential mating partners is not sufficient to engage the fertilization process. Linde and Selmes (2012) showed in Australian truffle orchards that about 40% of unproductive trees sustain mycorrhizas of both mating types. Factors other than the close vicinity of compatible gametes are thus necessary for fertilization to take place.…”
Section: How Do Gametes Of Opposite Mating Types Meet?mentioning
confidence: 99%
See 1 more Smart Citation
“…In some populations, only one mating type can be found under a single host tree (Murat et al 2013) (Table 1). In other populations, Rubini et al (2011a), Zampieri et al (2012), and Linde and Selmes (2012) found biased distributions of two mating types of Tuber truffles under a single tree. Because sexual reproduction in Tuber species requires the mating between strains of two different mating types, the mycetophagous mammals play an important role for this to occur by bringing sexual partners into the proximity of root resident strains (Kataržytė and Kutorga 2011).…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 95%
“…The success of some plantations is threatened by the accidental introduction of T. brumale (through the imported sporocarps used as inoculum) in both countries (Linde and Selmes, 2012;Guerin-Laguette et al, 2013).…”
Section: Australia and New Zealandmentioning
confidence: 99%